Enhancing pathogen description and antibiotic regimen selection in community-acquired pneumonia through RT-qPCR assays - Zhao, Na; Ren, Hongyu; Zhang, Yingmiao; Jiang, Yan; Deng, Jianping; Jiang, Luxi; Lu, Zhongxin; Qin, Tian (Frontiers in Microbiology, 2024)
Background: Adults with community‐acquired pneumonia (CAP) in China suffer high morbidity. CAP is caused by a multitude of pathogens; however, pathogen-directed clinical symptoms are often lacking. Therefore, patients lacking an accurate microbiological diagnosis are administered with empirical antimicrobials. Methods: We collected bronchoalveolar lavage fluid, as well as clinical and laboratory data from 650 adult patients with CAP admitted to three hospitals in Hubei, Sichuan, and Zhejiang provinces in China. Specimens were cultured and tested using RT-qPCR assays for the presence of 42 respiratory bacteria and viruses. CAP was investigated with respect to regions, genders, and age and patterns of infections or co-infections. Employing clinical guidelines adapted for diagnosis, we assessed retrospectively the appropriate pathogen-directed therapy and compared it with the initial empirical therapies. Results: Our study identified that 21.38% (139/650 ) of the patients were classified as having Severe CAP (S-CAP), with a higher prevalence among males, older adults, and during the warm season. Bacterial pathogens were detected in 35.53% (231/650) of cases. K. pneumoniae, H. influenzae, and S. aureus were the most prevalent bacteria across different demographics and regions. Viral pathogens were found in 48.76% (317/650) of patients Epstein-Barr, Human rhinovirus, and Cytomegalovirus were the most common viruses. Co-infections were present in 24.31% (158/650) of cases, with viral-bacterial co-infections being the most frequent. The RT-qPCR demonstrated significantly higher detection rates for key pathogens compared to standard culture methods. It showed potential in optimizing antimicrobial prescriptions by allowing for de-escalation in 18.30% (95/518) of patients, among which reducing the number of excessive antibiotics mainly comprised decreasing the use of 2nd or 3rd generation cephalosporins (5.79%, 30/518) and β-lactamase inhibitor combinations. Conclusions: The study highlights the significant burden of S-CAP, particularly among specific demographics and seasons. The prevalence of bacterial and viral pathogens, along with the high rate of co-infections, emphasizes the need for comprehensive diagnostic approaches. The RT-qPCR assays emerge as a superior diagnostic tool, offering enhanced pathogen detection capabilities and facilitating more precise antimicrobial therapy. This could lead to improved patient outcomes and contribute to the rational use of antimicrobials, addressing the growing concern of antibiotic resistance.